Optimization of mechanical and setting properties in acrylic bone cements added with graphene oxide (2021)
The extended use of acrylic bone cements (ABC) in orthopedics presents some disadvantages related to the generation of high temperatures during methyl methacrylate polymerization, thermal tissue necrosis, and low mechanical properties. Both weaknesses cause an increase in costs for the health system and a decrease in the patient’s quality of life due to the prosthesis’s loosening. Materials such as graphene oxide (GO) have a reinforcing effect on ABC’s mechanical and setting properties. This article shows for the first time the interactions present between the factors sonication time and GO percentage in the liquid phase, together with the percentage of benzoyl peroxide (BPO) in the solid phase, on the mechanical and setting properties established for cements in the ISO 5833-02 standard. Optimization of the factors using a completely randomized experimental design with a factorial structure resulted in selecting nine combinations that presented an increase in compression, flexion, and the setting time and decreased the maximum temperature reached during the polymerization. All of these characteristics are desirable for improving the clinical performance of cement. Those containing 0.3 wt.% of GO were highlighted from the selected formulations because all the possible combinations of the studied factors generate desirable properties for the ABC.